Alzheimer's disease susceptibility genes APOE and TOMM40, and hippocampal volumes in the Lothian birth cohort 1936. - Donald M Lyall; Natalie A Royle; Sarah E Harris; Mark E Bastin; Susana Muñoz Maniega; Catherine Murray; Michael W Lutz; Ann M Saunders; Allen D Roses; Maria C del Valdés Hernández; John M Starr; David J Porteous; et al. (PLoS ONE)
The APOE ε and TOMM40 rs10524523 ('523') variable length poly-T repeat gene loci have been significantly and independently associated with Alzheimer's disease (AD) related phenotypes such as age of clinical onset. Hippocampal atrophy has been significantly associated with memory impairment, a characteristic of AD. The current study aimed to test for independent effects of APOE ε and TOMM40 '523' genotypes on hippocampal volumes as assessed by brain structural MRI in a relatively large sample of community-dwelling older adults. As part of a longitudinal study of cognitive ageing, participants in the Lothian Birth Cohort 1936 underwent genotyping for APOE ε2/ε3/ε4 status and TOMM40 '523' poly-T repeat length, and detailed structural brain MRI at a mean age of 72.7 years (standard deviation = 0.7, N range = 624 to 636). No significant effects of APOE ε or TOMM40 523 genotype were found on hippocampal volumes when analysed raw, or when adjusted for either intracranial or total brain tissue volumes. In summary, in a large community-dwelling sample of older adults, we found no effects of APOE ε or TOMM40 523 genotypes on hippocampal volumes. This is discrepant with some previous reports of significant association between APOE and left/right hippocampal volumes, and instead echoes other reports that found no association. Previous significant findings may partly reflect type 1 error. Future studies should carefully consider: 1) their specific techniques in adjusting for brain size; 2) assessing more detailed sub-divisions of the hippocampal formation; and 3) testing whether significant APOE-hippocampal associations are independent of generalised brain atrophy.